The interpersonal skills and leadership styles of supervisory librarians in U.P. Diliman - Resurreccion, Irene S. (Institute of Library Science, University of the Philippines Diliman, 2001)
The objectives of this study are the following: 1) To determine the interpersonal skill level of supervisory librarians in U.P. Diliman; 2) To determine their different leadership styles; and 3) To determine the relationship of educational attainment and length of work experience to interpersonal skill.